Hdh-Tektin-4 Regulates Motility of Fresh and Cryopreserved Sperm in Pacific Abalone, Haliotis discus hannai - Sukhan, Zahid Parvez; Hossen, Shaharior; Cho, Yusin; Lee, Won Kyo; Kho, Kang Hee (Frontiers in Cell and Developmental Biology, 2022)
As structural components of sperm, tektins are thought to play a fundamental role in sperm flagellar motility. In the present study, tektin-4 (Hdh-TEKT4) gene was successfully cloned and characterized from testis tissue in Pacific abalone, Haliotis discus hannai. The full-length cDNA of Hdh-TEKT4 was 1983 bp, with a coding region of 1350 bp encoding 51.83 kDa putative protein of 449 deduced amino acids. Hdh-TEKT4 contains a tektin domain including a nonapeptide signature motif (RPGVDLCRD). Fluorescent in-situ hybridization revealed that Hdh-TEKT4 localized in the spermatids of Pacific abalone testis. qRT-PCR analysis shown that Hdh-TEKT4 was predominantly expressed in testis tissues. Hdh-TEKT4 mRNA expression was upregulated during fully mature testicular developmental stage in both seasonal development and EAT exposed abalone. Furthermore, mRNA expression of Hdh-TEKT4 was significantly higher in sperm with higher motility than in sperm with lower motility during peak breeding season, induced spawning activity stages and after cryopreservation in different cryoprotectant. Taken together, these results indicate that the expression of Hdh-TEKT4 in Pacific abalone sperm might have a positive correlation with sperm motility.